SINGLE PHOTON EMISSION COMPUTED TOMOGRAPHY IN DIAGNOSTICS OF OBSTRUCTIVE LESION IN CORONARY ARTERIES - A. N. Sumin; E. V. Korok; A. A. Korotkevich; E. N. Kachurina; A. N. Kokov; O. L. Barbarash (Российский кардиологический журнал, 2017)
Aim. To evaluate the potential of single photon emission computed tomography (SPECT) in diagnostics of obstructive lesion of coronary arteries (CA).Material and methods. The studied group consisted of 107 patients, admitted for diagnostics and treatment in the SRI CICVD during 2012-2015 with former established diagnosis of coronary heart disease (CHD) or hospitalized to rule it out. For hemodynamically significant stenoses, coronary arteriography (CAG) was applied. Data from CAG was compared with SPECT. As a result, four groups were formed: 1 group — with positive results by SPECT and CAG (SPECT“+”/CAG“+”, n=24); 2 group — with positive SPECT and negative CAG (SPECT“+”/CAG“-”, n=6); 3 group — with negative SPECT and positive CAG (SPECT“-”/CAG“+”, n=36); 4 group — negative both SPECT and CAG (SPECT“-”/CAG“-”, n=41).Results. In assessment of the patients with suspected CHD, positive result of pharmacological stress-test in SPECT was revealed in 28% cases, and hemodynamically significant CA lesion was found in 56% of patients. Myocardial infarction in anamnesis predominated in SPECT“+”/CAG“+” (79,2%), SPECT“+”/CAG“-” (83,3%), SPECT“-”/CAG“+” (55,6%) comparing to SPECT“-”/CAG“-” (39%; р=0,007). Also, in the group SPECT“-”/CAG“-” pre-test probability of CHD was the lowest (58%) comparing to other groups — 80,5%; 80,5% and 77% (р=0,002). Hence ejection fraction of the left ventricle was significantly lower in the group of SPECT“+”/CAG“+” (53%; р=0,011). In this group also subocclusion was found in circumflex (29,2%) and right CA (45,8%), respectively, р=0,033 and р=0,054. With the false negative results of SPECT there was association of male gender, former coronary bypass operation, increased cardiac volume. Sensitivity of SPECT in hemodynamically significant CA stenoses diagnostics was 40%, specificity — 87%.Conclusion. The results of current study are important for further elaboration on the approaches to obstructive CHD diagnostics.